Γ-[Glu](n=1, 2)-Phe/-Met/-Val stimulates gastrointestinal hormone (CCK and GLP-1) secretion by activating the calcium-sensing receptor. Issue 7 (21st June 2019) - Yang, Juan; Bai, Weidong; Zeng, Xiaofang; Cui, Chun
Abstract : This study was conducted to discover the effectiveness of dietary peptides (γ-[Glu]( n =1, 2) -Phe/-Met/-Val) as stimulators of cholecystokinin (CCK) and glucagon-like peptide 1 (GLP-1) secretion. Abstract : This study was conducted to discover the effectiveness of dietary peptides (γ-[Glu]( n =1, 2) -Phe/-Met/-Val) as stimulators of cholecystokinin (CCK) and glucagon-like peptide 1 (GLP-1) secretion. The kokumi-active γ-[Glu]( n =1, 2) -Phe/-Met/-Val at concentrations of 2.5–10 mM would trigger the release of CCK and GLP-1 by activating the calcium-sensing receptor (CaSR). The CaSR-mediated Ca 2+ /CaM/CaMK pathway was proposed in γ-[Glu]( n =1, 2) -Phe/-Met/-Val-induced CCK and GLP-1 secretion based on the following results: the exposure to γ-Glu-Phe increased the protein expression level (western blot analysis), the intracellular calcium ([Ca 2+ ]i ) mobilization in response to γ-[Glu]( n =1, 2) -Phe/-Met/-Val was strongly enhanced, and the inhibitors of signaling pathway proteins (NPS-2143, BAPTA-AM, and KN62) abolished partially γ-[Glu]( n =1, 2) -Phe/-Met/-Val-induced CCK and GLP-1 secretion.